LINGKUNGAN YANG DAPAT MEMPENGARUHI TUMBUHNYA MOTIVASI DAN KEBERHASILAN STUDI ANAK DAN REMAJA DALAM PERSPEKTIF SOSIOLOGI - Fata, Nahriyah (FORUM PAEDAGOGIK, 2014)
The focus of this simple written arround in aspect various social area that can influenced growed of motivation and students successful study in child and teenagers, both of them that an individual could easy to influence and the behaviorisme who lived grow up together. In the authentic there is the influnce can kick and hamper and both of them could be explained with revealed the hope action from that the behaviorisme could be expressed in the circle behavioral model. Although in the area focus investigate in this written are: family circle, playing group, school circle that investigated with sosiology approach especially about action of the intraction child and teenager concept with that area. Althought because parents busy or less in knowledge and time together with child and teenager cause action of this area do not respected. So,through this simple written hoped the introduced that area could be given suggest for the educator can minimized the negative influnce or who can hampered motivation dan the successful study of them.